Burden and unmet needs in asthma care in the Asia‐Pacific region - Surbhi Wadhawan; Umadevi A. Muthukumaru; Li Cher Loh (Wiley, 2022)
Abstract Asthma is a chronic respiratory disease with increasing global prevalence. It affects approximately 300 million people globally and more than a third of these patients have uncontrolled asthma. The burden of poorly controlled asthma is considerable both for the individuals and the society. The World Health Organization (WHO) estimates that, 455,000 people died from asthma worldwide in 2019, the majority in low and low‐middle‐income countries. This article highlights the unmet needs and burden of asthma in the Asia‐Pacific region where many patients have poorly controlled asthma despite advances in asthma care and treatment. A mismatch between patients' (and physicians') perception of asthma control and optimal asthma control as defined by the Global Initiative for Asthma (GINA) is a challenge in the real‐life management of many patients. Consequently, treatment adherence and optimization are affected. In many of these aspects, patients with asthma in the Asia‐Pacific region are comparatively worse than those from Europe and North America. In future, cooperation of all stakeholders is needed in improving awareness, education, and goal‐directed management of asthma with meaningful improvement in quality of life. This article draws attention to some of the important gaps in asthma management in the Asia‐Pacific region and suggests some measures to address these unmet needs.